pegegog 2022
DOI: 10.47750/pegegog.12.04.09
|View full text |Cite
|
Sign up to set email alerts
|

Model mental transition-attempting: The case of beginners students in understanding the concept of integers

Abstract: A mental model is a concept that exists in students' minds and is used to describe and explain a phenomenon. This study aims to describe the transition-attempting mental model of students in understanding the concept of integers. This study uses a qualitative approach and the type of research conducted is descriptive. The subjects of this study amounted to 58 students in class VII. Subjects were given a test to determine their understanding of the concept of integers. They were collecting data in this study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The researcher found that most students could compare negative and positive integers with the same quantity symbol. From the results of this analysis and study, it will be possible for students to be able to compare whole numbers with different quantity symbols (Sukiyanto et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The researcher found that most students could compare negative and positive integers with the same quantity symbol. From the results of this analysis and study, it will be possible for students to be able to compare whole numbers with different quantity symbols (Sukiyanto et al, 2022).…”
Section: Discussionmentioning
confidence: 99%